2009
DOI: 10.5194/angeo-27-2491-2009
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of thermospheric dynamics: divergence as a proxy for vertical winds

Abstract: Abstract.A local scale, time dependent three-dimensional model of the neutral thermosphere was used to test the applicability of two previously published empirical relations between thermospheric vertical wind and velocity divergence, i.e., those due to Burnside et al. (1981) and Brekke (1997). The model self-consistently solves for vertical winds driven by heat and momentum deposited into the neutral atmosphere by high latitude ion convection. The Brekke condition accurately mimicked the overall "shape" of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Similarly, other studies have found that the Burnside relation can, in fact, break down under strong disturbances in the high‐latitudes [ Crickmore , 1993; Smith and Hernandez , 1995]. For instance, using a time‐dependent three‐dimensional local model of the thermosphere, Cooper et al [2009] have investigated the applicability of the Burnside et al [1981] relation. They have found that although the Burnside et al [1981] condition is usable under slowly varying conditions above the F region peak, it is applicable to a limited extent when the high‐latitude forcing is varying rapidly in time.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly, other studies have found that the Burnside relation can, in fact, break down under strong disturbances in the high‐latitudes [ Crickmore , 1993; Smith and Hernandez , 1995]. For instance, using a time‐dependent three‐dimensional local model of the thermosphere, Cooper et al [2009] have investigated the applicability of the Burnside et al [1981] relation. They have found that although the Burnside et al [1981] condition is usable under slowly varying conditions above the F region peak, it is applicable to a limited extent when the high‐latitude forcing is varying rapidly in time.…”
Section: Discussionmentioning
confidence: 94%
“…A number of authors have studied the relationship between the vertical winds and the divergence of the horizontal winds [ Burnside et al , 1981; Biondi , 1984; Crickmore , 1993; Cooper and Conde , 2006; Cooper et al , 2009]. The advantages of a nonhydrostatic model such as GITM in studying thermospheric vertical winds and their variability are, among others, (1) high model time resolution of 2–4 s, (2) the individual vertical momentum flux deposition terms can be investigated in detail, (3) the significance of nonhydrostatic acceleration can be quantified, (4) the temporal variations of the horizontal wind divergence can be compared with that of the vertical winds and other thermospheric parameters.…”
Section: Discussionmentioning
confidence: 99%
“…[46] Cooper et al [2009] tested the validity of equation (5) using a local-scale, time-dependent, three-dimensional model of the neutral atmosphere and found that it was generally only applicable above the height of maximum energy and momentum deposition per unit mass, and at times when the forcing did not change rapidly with time. Below the height of maximum forcing the Burnside condition predicted the incorrect sign for the vertical wind.…”
Section: Discussionmentioning
confidence: 99%
“…Numerical models of localized heating are widely used in case studies. For example, Cooper et al [] included Joule heating in a local‐scale model of vertical thermospheric winds. Davies et al [] compared ISR measurements with results from the Sheffield University Plasmasphere and Ionosphere Model, calculating parameters along a single magnetic field line.…”
Section: Introductionmentioning
confidence: 99%